The utility and limitations of neurosphere assay, CD133 immunophenotyping and side population assay in glioma stem cell research - Wan, Feng; Zhang, Suojun; Xie, Ruifan; Gao, Baocheng; Campos, Benito; Herold-Mende, Christel; Lei, Ting (Brain pathology, 2010)
The newly proposed glioma stem cell (GSC) hypothesis may re-model the way we diagnose and treat the tumor, which highlights the need for a complete knowledge on the genetic and epigenetic “blueprints” of GSCs. To identify the true “stemness” signatures, pure GSC populations are primarily needed. Reliable in vitro methods enriching for GSCs and thereby identifying the key stem-like characteristics constitute the preliminary step forward. We discuss in this review the current widely used methods for enriching and isolating GSCs, namely neurosphere assay, CD133 Immunophenotyping and side population assay, and detail their limitations and potential pitfalls that could complicate interpretation of corresponding results.
Gesehen am 10.10.2023